(untitled) (Estudos em Design, 2023)
Editores Cristina Portugal Rita Maria de Souza Couto Avaliadores desta edição v. 31, n. 2 (2023) Adriana Gralow Adriana Sampaio Leite Alexandre Farbiarz Alexandre Oliveira Aline Savi Álvaro Sousa Ana Beatriz Pereira de Andrade Ana Berwanger Ana Pazmino André Ribeiro de Oliveira Andréa Almeida Andréa Silva Angelica Adverse Antonio Colchete Filho Beany Monteiro Carlo Franzato Cassia Carrara Domiciano Cayley Guimaraes Cristiane Aun Bertoldi Cyntia Malaguti de Sousa Deborah Christo Daniel Portugal Daniel Raposo Daniela Estaregue Alves Debora Buonano Denise Portinari Doris Kosminsky Edson Rufino Emília Duarte Everton da Silva Fernanda Cardoso Fernando Fogliano Filipe Campelo Xavier da Costa Frederico Braida Gabriel Patrocinio Gabriela Perry Giselle Merino Guilherme E nglert Corrêa Meyer Helena Barbosa Ione Bentz Jade Piaia Joana Contino João Sobral Karina Porto Bontempo Kando Fukushima Kátia Carvalhaes Pêgo Klaus Alberto Laura Martins Luiz Antonio de Saboya Livia Flavia Campos Luiza Falcão Soares Cunha Marcelo Forcato Marcio Guimarães Marcos Braga Maria Do Carmo Gonçalves Curtis Maria Teresa Lopes Marilda Lopes Pinheiro Queluz Mariano Lopes de Andrade Neto Marina Kunst Maristela Ono Maurício Klafke Dick Nelson Kuwahara Olavo Neto Paula Piva Linke Rafael Efrem Rafaella Peres Raimundo Diniz Ranielder de Freitas Ravi Passos Renata Wanderley Rogério Camara Sandra Maria Souza Sérgio Luciano da Silva Tiago Silva Wagner Bandeira Walter Correia Vagner Godói Walter Neto Vera Damazio Verônica Freire Virginia Kistmann Viviane Nunes